Introduction to Islamic Banking - Ameer, U.A. (Islamic publishing house, 2016)
The book contains a brief history of Islamic banking industry with brief descriptions of Islamic banking products and the stands of the shariah scholars towards these products...
Islamiya vankiyiyal oar arimukam
Keywords: Banking